Jurutera December 2019 Working Towards the Future with IoT - Ahmad, Yasser Asrul (The Institution of Engineers, Malaysia (IEM) and Dimension Publishing Sdn Bhd, 2019)
The Internet of Things (IoT) can be defined as extending the connectivityof devices or things to the internet. This is becoming feasible due to easy access to the internet. IoT has potential applications in many areas, including agriculture, medical & healthcare, consumer products, industries and smart cities. Soon, we will see IoT integration in almost every aspect of our daily lives. The huge amount of data generated by IoT sensors will see a convergence with big data platforms. Data analytics will become essential for extracting information in the form of trends, patterns or statistics to help individuals, professionals and organisations make effective and informed decisions. Big data, artificial intelligence and IoT may work together to make “things” autonomous, such as the self-driving cars. IoT can be implemented via existing wireless networks such as WiFi, LoRa, Long-Term Evolution (LTE) and 4G but its full potential is expected to be unleashed with 5G mobile services which will offer faster data rates, lower latency and bigger bandwidth. The challenge is to provide full-scale 5G deployments and overcome propagation effects. The vast potential of IoT has prompted IEM to forge a digital partnership with Malaysia Digital Economy Corporation (MDEC) and establish IEM Makerspace. A digital maker hub at Wisma IEM for engineers, educators and students to work on common digital interest. It will also promote awareness in engineering to school children using STEM activities focusing on physical computing, software development, creative media and engineering & design.